Catholicism and religious freedom: renewing the church in the Second Vatican Council - Gabriel, Karl (Schöningh, Fink and mentis Religious Studies, Theology and Philosophy E-Books Online, Collection 2019, ISBN: 9783657100170, 2019)
Front Matter -- Copyright page /Karl Gabriel , Christian Spiess and Katja Winkler -- Foreword /José Casanova -- Introduction /Karl Gabriel , Christian Spiess and Katja Winkler -- Dignitatis humanae: Development of the Text /Karl Gabriel , Christian Spiess and Katja Winkler -- Modernity – Religion – Catholicism /Karl Gabriel , Christian Spiess and Katja Winkler -- Religious Freedom /Karl Gabriel , Christian Spiess and Katja Winkler -- Continuity – Change – Break? /Karl Gabriel , Christian Spiess and Katja Winkler -- Factors of Change /Karl Gabriel , Christian Spiess and Katja Winkler -- The Path to Recognizing Religious Freedom as a Two-stage Learning Process /Karl Gabriel , Christian Spiess and Katja Winkler -- Back Matter -- References /Karl Gabriel , Christian Spiess and Katja Winkler -- Acknowledgements /Karl Gabriel , Christian Spiess and Katja Winkler.